2017
DOI: 10.1007/978-3-319-52727-7_10
|View full text |Cite
|
Sign up to set email alerts
|

Formulating A Global Identifier Based on Actor Relationship for the Internet of Things

Abstract: The Internet of Things (IoT) promising a new generation of services been offered to a human being through a world of interconnected objects (called "things") that may use different communication technologies. Objects, in IoT, are seamlessly connected on its owner/user behalf. To offer services, the service providers need to truly identify the effective actor/user rather than the communicated devices. Currently, users have relationships with multiple objects that can also be used to determine their user. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…One of such methods, regarding device identification, is demonstrated by [18]. Making use of the formal method and set theory, allowed [18,19] to simply utilise previous terms as well as develop novel terms and formulae for a Universal Identification Number (UID) for IoT devices which he referred to as the Global Actor Relationship Identifier (GARI) method. For this process, the methods utilised, allowed to approach the issues of IoT device management and identification in the most sensible way.…”
Section: Universal Identification Number and Set Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…One of such methods, regarding device identification, is demonstrated by [18]. Making use of the formal method and set theory, allowed [18,19] to simply utilise previous terms as well as develop novel terms and formulae for a Universal Identification Number (UID) for IoT devices which he referred to as the Global Actor Relationship Identifier (GARI) method. For this process, the methods utilised, allowed to approach the issues of IoT device management and identification in the most sensible way.…”
Section: Universal Identification Number and Set Theorymentioning
confidence: 99%
“…These pieces of evidence are very crucial during an investigation, be it a physical or digital one. Previous research has suggested methods to manage IoT devices globally, however, these did not consider variables such as the implementation of identification numbers in an IoT Forensics environment, which is of high necessity in today's day and age of SC and the IoT usage increase [19]. Our proposed idea suggests, an approach similar to DNA analysis regarding IoT forensics, however, instead of using traditional DNA, as we are talking about technology, we propose a method to allocate a unique identification number to IoT devices worldwide.…”
Section: A Model Of Devices' Dna and Genesmentioning
confidence: 99%
“…The problem of assigning identity to devices is described in [47]. An IoT device inherits the identity of its user through various methods based on a relationship between the user and the device.…”
Section: Identity Managementmentioning
confidence: 99%
“…Most of the surveyed proposals contain an identity management, authentication, or authorization service. An application in the IoT environment may offload the authentication process to such a security service [16,17,21,23,27,32,35,47]. A few proposals also allow the distribution of access rights or other properties used for authorization from the service to its clients [15,21,46].…”
Section: Servicesmentioning
confidence: 99%